Consulta pública eletrônica e a LINDB: a construção da cidadania participativa digital na edição dos atos normativos federais do sistema único de assistência social - Paganini, Juliana (Universidade do Vale do Rio dos Sinos, 2025)
This research analyzed the conditions under which the use of electronic public consultation under the Law of Introduction to the Norms of Brazilian Law (LINDB), in the publication of federal normative acts for the Unified Social Assistance System (SUAS), constitutes a prerequisite for strengthening participatory digital citizenship in the Brazilian Public Administration. The history of Public Administration has been marked by patrimonialist practices, in which public assets were conflated with private interests and decisions were made in a hierarchical and centralized manner. Although, over time, the country has transitioned to bureaucratic, managerial, social (societal), and, to some extent, electronic public management models, patrimonialist traits still persist, limiting popular participation to a passive stance regarding the decisions of elected officials. The 1988 Constitution of the Federative Republic of Brazil (CRFB/1988) established three forms of exercising popular sovereignty: indirect, direct, and semi-direct. And even though indirect participation, through political representation, is the most common, there is growing social dissatisfaction with administrative decisions made top-down and without dialogue with society. This scenario reinforces the urgency of expanding channels for citizen participation, especially in the development of administrative normative acts. This is because, with the amendment of the LINDB in 2018, Article 29 now provides for the possibility of conducting public consultations prior to the issuance of normative acts by the Public Administration, in all spheres. However, in the field of social assistance, despite its recognition as a right—and no longer a favor—by the 1988 CRFB (Brazilian Constitution) and the fact that the importance of public participation is enshrined in both the SUAS and the National Social Assistance Policy (PNAS), the implementation of this participation remains limited. Although the Ministry of Development and Social Assistance, Family, and Fight against Hunger (MDS), through the National Secretariat of Social Assistance (SNAS), launched the Normative Acts Management System in 2020 to bring together the SUAS and PNAS regulations on a single platform for public consultation, this instrument did not address participatory citizenship, as its merely advisory nature lacks mechanisms that enable direct public intervention in the regulatory process. Therefore, the research question relates to the overall objective, as the guiding question of this thesis seeks to determine: under what conditions does the use of the LINDB electronic public consultation system (LINDB) in the publication of federal SUAS normative acts constitute a prerequisite for strengthening digital participatory citizenship in the Brazilian Public Administration? The hypothesis is that this would be possible through an intuitive and accessible electronic platform that provides a space open to popular participation, respecting the constitutional parameters of the Democratic Rule of Law. The specific objectives were: a) to present the trajectory of Brazilian Public Administration and its transformations with the advent of the Information Society in the Democratic State of Law; b) to study the lack of popular participation in the process of publishing and consulting federal regulatory acts of the SUAS (National Health System) in light of the Information Society; and c) to propose a new form of management capable of contributing to the consolidation of Brazilian digital participatory citizenship, considering the use of the LINDB electronic public consultation in the publishing of federal regulatory acts of the SUAS. The research adopted the deductive approach and the monographic procedure method, using bibliographic and documentary research techniques. The results demonstrated that, despite the existence of the "Participa + Brasil" and "Brasil Participativo" platforms as tools for public consultation on public policies, both have weaknesses. Therefore, the creation of the "Consulta SUAS" platform is proposed, which will contribute to the consolidation of public management less guided by patrimonialist practices and more guided by an electronic Public Administration. Thus, it is expected that the use of the electronic public consultation provided for in article 29 of the LINDB will be effectively incorporated as a tool for democratizing federal regulatory processes within the scope of SUAS, thus strengthening digital participatory citizenship in Brazil.

Esta investigación analizó las condiciones bajo las cuales el uso de la consulta pública electrónica, de conformidad con la Ley de Introducción a las Normas del Derecho Brasileño (LINDB), en la publicación de actos normativos federales del Sistema Único de Asistencia Social (SUAS), constituye un prerrequisito para el fortalecimiento de la ciudadanía digital participativa en la Administración Pública brasileña. La historia de la Administración Pública ha estado marcada por prácticas patrimonialistas, en las que los bienes públicos se fusionaban con los intereses privados y las decisiones se tomaban de forma jerárquica y centralizada. Si bien, con el tiempo, el país ha transitado hacia modelos de gestión pública burocráticos, gerenciales, sociales (societales) y, en cierta medida, electrónicos, aún persisten rasgos patrimonialistas, que limitan la participación popular a una postura pasiva ante las decisiones de los funcionarios electos. La Constitución de la República Federativa del Brasil de 1988 (CRFB/1988) estableció tres formas de ejercicio de la soberanía popular: indirecta, directa y semidirecta. Y si bien la participación indirecta, a través de la representación política, es la más común, existe una creciente insatisfacción social con las decisiones administrativas tomadas verticalmente y sin diálogo con la sociedad. Este escenario refuerza la urgencia de ampliar los canales de participación ciudadana, especialmente en la elaboración de actos normativos administrativos. Esto se debe a que, con la modificación de la LINDB en 2018, el artículo 29 ahora prevé la posibilidad de realizar consultas públicas previas a la emisión de actos normativos por parte de la Administración Pública, en todos los ámbitos. Sin embargo, en el ámbito de la asistencia social, a pesar de su reconocimiento como un derecho —y ya no como un favor— por la CRFB (Constitución de Brasil) de 1988 y de que la importancia de la participación popular está consagrada tanto en la SUAS (Política Nacional de Asistencia Social) como en la Política Nacional de Asistencia Social (PNAS), la implementación de esta participación sigue siendo limitada. Aunque el Ministerio de Desarrollo y Asistencia Social, Familia y Combate al Hambre (MDS), a través de la Secretaría Nacional de Asistencia Social (SNAS), lanzó el Sistema de Gestión de Actos Normativos en 2020 para reunir las regulaciones del SUAS y PNAS en una única plataforma de consulta pública, este instrumento no abordó la ciudadanía participativa, ya que su naturaleza meramente consultiva carece de mecanismos que permitan la intervención pública directa en el proceso regulatorio. Por lo tanto, la pregunta de investigación se relaciona con el objetivo general, ya que la pregunta guía de esta tesis busca determinar: ¿bajo qué condiciones el uso del sistema electrónico de consulta pública LINDB (LINDB) en la publicación de los actos normativos federales del SUAS constituye un prerrequisito para el fortalecimiento de la ciudadanía participativa digital en la Administración Pública brasileña? La hipótesis es que esto sería posible a través de una plataforma electrónica intuitiva y accesible que brinde un espacio abierto a la participación popular, respetando los parámetros constitucionales del Estado Democrático de Derecho. Los objetivos específicos fueron: a) presentar la trayectoria de la Administración Pública brasileña y sus transformaciones con el advenimiento de la Sociedad de la Información en el Estado Democrático de Derecho; b) estudiar la falta de participación ciudadana en el proceso de publicación y consulta de las leyes regulatorias federales del SUAS (Sistema Único de Salud) en el contexto de la Sociedad de la Información; y c) proponer una nueva forma de gestión que contribuya a la consolidación de la ciudadanía digital participativa brasileña, considerando el uso de la consulta pública electrónica LINDB en la publicación de las leyes regulatorias federales del SUAS. La investigación adoptó el enfoque deductivo y el método monográfico, empleando técnicas de investigación bibliográfica y documental. Los resultados demostraron que, a pesar de la existencia de las plataformas "Participa + Brasil" y "Brasil Participativo" como herramientas de consulta pública sobre políticas públicas, ambas presentan debilidades. Por lo tanto, se propone la creación de la plataforma "Consulta SUAS", que contribuirá a la consolidación de una gestión pública menos orientada por prácticas patrimonialistas y más orientada por una Administración Pública electrónica. De esta forma, se espera que el uso de la consulta pública electrónica prevista en el artículo 29 del LINDB se incorpore eficazmente como herramienta para democratizar los procesos regulatorios federales en el ámbito del SUAS, fortaleciendo así la ciudadanía digital participativa en Brasil.
Keywords: Atos Normativos Federais; Cidadania Participativa Digital; Consulta Pública Eletrônica; LINDB; SUAS; Federal Normative Acts; Digital Participatory Citizenship; Electronic public consultation; Leyes Normativas Federales; Ciudadanía Participativa Digital; Consulta pública electrónica; ACCNPQ::Ciências Sociais Aplicadas::Direito